Listeria rhomboencephalomyelitis complicated by haemorrhagic transformation. Issue 5 (8th May 2017) - Nham, Benjamin; Baskin, Johnathan; Choong, Ho
Abstract : Objectives: We report a case of Listeria sepsis with highlights: 1) Concurrent rhomoboencephalitis and cervical myelitis complicated by haemorrhagic transformation, 2) Clinical and radiological improvement following substitution of benzylpenicillin with both ampicillin and double strength sulfamethoxazole/trimethoprim. Listeria monocytogenes infection is a rare but well documented cause of central nervous system infection which typically manifests as meningoencephalitis, but less commonly can cause rhomboencephalitis or myelitis. Case: A 53 year-old woman presented with a 2 weeks history of vertigo, diplopia, fevers and ataxia. She denied other localising infective symptoms. Examination revealed dysarthria, bidirectional nystagmus, bifacial numbness, right sided pyramidal weakness and dysmetria. She was commenced on meningitis doses of ceftriaxone and benzylpenicillin. Blood cultures were positive for Listeria monocytogenes as was Listeria PCR on CSF. Antibiotics were switched to benzylpenicillin and gentamycin as per guidelines. MRI revealed T2 hyper-intense areas involving the cerebellum and cerebellar peduncles, inferolateral pons and medulla. The hyper intensities also involved the upper cervical cord up to C8. Interval MRI demonstrated small areas of haemorrhage within the brainstem and spinal cord lesions. Given limited early clinical improvement, the antibiotics were switched to intravenous ampicillin and double strength sulfamethoxazole/trimethoprim was later added. A total of 6 weeks of antibiotics were given with significant clinical improvement and resolution of the MRI hyperintensities. Conclusions: Concurrent Listeria myelitis with rhomboencephalitis has not been reported. Furthermore, the corresponding MRI hyperintensities demonstrated haemorrhagic transformation without abscess formation is a novel finding, likely secondary to bacterial invasion or localised necrotic inflammation of blood vessels leading to exudation of blood products. First line treatment of CNS Listeriosis is either ampicillin or benzylpenicillin with sulfamethoxazole/trimethoprim as second line treatment. Consideration of switching antibiotics in the event of inadequate clinical improvement can be trialled as Australian guidelines differ from international ones.